A Prehistory of Polymer Science - Carnegie Mellon University, Gary Patterson; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Polymer science is now an active and thriving community of scientists, engineers and technologists, but there was a time, not so long ago, when there was no such community. The prehistory of polymer science helps to provide key insights into current issues and historical problems. The story is divided into an ancient period, from Greek times to the creation of the molecular consensus, a nascent period, from Dalton to Kekule to van$1 (Bt Hoff, and a period of paradigm formation and controversy, from Staudinger to Mark to Carothers. The prehistory concludes with an account of the epochal 1935 Discussion of the Faraday Society on (3z(BPolymerization.(3y (BAfter this meeting an active community engaged in trying to solve the central problems defined by the discussions.s
Ancient Period -- Nascent Period -- Period of Paradigm Formation -- The Age of Macromolecules.
Keywords: Chemistry; Science -- History; Polymers; History; Chemistry; Polymer Sciences; History of Science; History